Thrombin generation and intracranial atherosclerotic disease in patients with a transient ischaemic attack. Issue 155 (July 2017) - Favaretto, Elisabetta; Sartori, Michelangelo; Legnani, Cristina; Rondelli, Francesca; Cini, Michela; Guarino, Maria; Cosmi, Benilde
Abstract: Background: Intracranial atherosclerotic disease (ICAD) is responsible for at least 10% of transient ischaemic attacks (TIA). Thrombin generation has been shown to be associated with several atherosclerotic conditions and may be relevant in the pathogenesis of TIA from ICAD. Objective: To evaluate the association between thrombin generation and ICAD in patients with TIA. Materials and methods: Consecutive patients with confirmed diagnosis of TIA by vascular neurologist were enrolled. Within 24 h from diagnosis, all the patients underwent: blood samples including thrombin generation search, electrocardiography, brain CT scan, blood pressure (BP) measurement, supra-aortic echo-Doppler, transcranial Doppler (TCD) and standard echocardiogram. Thrombin generation was measured as endogenous thrombin potential (ETP) in platelet-rich plasma (PRP) and in platelet-poor plasma (PPP), in the presence and in the absence of thrombomodulin (TM). Results: 120 patients (male 52.5%), aged 69 ± 16 years were enrolled. Ten patients on warfarin treatment had significantly lower ETP than the others. Among the remaining, ETP in the presence or absence of TM did not differ according to TOAST classification aetiology (large vessel vs. cardioembolic vs. lacunar vs. others). In PRP, ETP was similar in patients with ICAD and in those without (1748 ± 160 vs. 1851 ± 36 nM·min, p = 0.393), whereas, ETP measured in presence of thrombomodulin was higher in patients with than in those without ICAD (2045 ± 99 vs. 1715 ± 41 nM·min, p = 0.011). In PPP, ETP was similar in patients with ICAD and in those without, whereas thrombin peak was higher in patients with ICAD than in those without both in the presence (165 ± 17 vs. 130 ± 5 nM, p = 0.036) and in the absence of TM (178 ± 19 vs. 142 ± 5 nM, p = 0.037). Conclusion: ETP measured in presence of TM is enhanced in patients with ICAD, supporting that thrombomodulin-protein C pathways is relevant in TIA from ICAD. These hypothesis-generating data suggest that thrombin generation may be relevant in cerebral ischaemia from intracranial disease, and justify larger studies. Highlights: Intracranial atherosclerotic disease (ICAD) is responsible for at least 10% of transient ischaemic attacks (TIA). Thrombin generation measured in presence of thrombomodulin is enhanced during the acute phase of TIA from ICAD. Thrombomodulin-protein C pathways may be relevant in TIA from thrombosis of intracranial vessels.